Fertilization modifies forest stand growth but not stand density: consequences for modelling stand dynamics in a changing climate. (30th July 2021) - Pretzsch, Hans; Biber, Peter
Abstract: Knowledge of the maximum forest stand density and the self-thinning process is important for understanding, modelling and scheduling thinnings in silviculture. The upper trajectories of stem number, N, vs mean diameter, dq or mean tree volume vs stem number are often used for quantifying maximum stand density. The long debate about how site conditions modify these relationships is presently revived due to global change. A crucial question is whether environmental conditions alter the trajectories themselves or just the velocity at which stands move along them. Our contribution is based on fully stocked plots from long-term Scots pine ( Pinus sylvestris L.) fertilization experiments along an ecological gradient in South Germany. This allows us to compare the self-thinning trajectories of fertilized and unfertilized plots under different environmental conditions. We can show that repeated fertilization with nitrogen did not change the N ~ dq trajectories. Assuming that fertilization affects forests in a similar way as an ongoing atmospheric N -deposition, this means that presently growth, mortality, and volume accumulation in forest stands proceed faster in time but still follow the same N ~ dq allometric trajectories. Furthermore, we found that the level of the self-thinning line generally increases with the annual precipitation. The allometric self-thinning exponent, however, did not respond to environmental conditions. Finally, we quantitatively demonstrate and discuss the implications and consequences of the results regarding understanding and modelling forest stand dynamics, carbon sequestration and the development and adaptation of silvicultural guidelines in view of climate change.